The lack of reading comprehension practice in Primary Colors three and four textbooks affects the improvement of the reading comprehension skill of students of speak up kids 4 and speak up kids 5 levels at “Servicios Educativos Integrados” Speak Up Center, School Year 2009-2010. - GONZÁLEZ MALLA, EDUARDO FRANCISCO (2010)
In the present research about: “THE LACK OF READING COMPREHENSION PRACTICE IN PRIMARY COLORS THREE AND FOUR TEXTBOOKS AFFECTS THE IMPROVEMENT OF THE READING COMPREHENSION SKILLS OF STUDENTS OF SPEAK UP KIDS 4 AND SPEAK UP KIDS 5 LEVELS AT “SEVICIOS EDUCATIVOS INTEGRADOS” SPEAK UP CENTER, SCHOOL YEAR 2009-2010”, we set up the following general objective to determine how the lack of the reading comprehension practice in primary colors textbooks three and four affects the improvement of the reading comprehension skills of students from speak up kids 4 and speak up kids 5 levels at “Servicios Educativos Integrados”. We used the following methods: Scientific, Inductive, Deductive, Historical, Hypothetical-deductive, and Descriptive. To collect the required data, we used the following techniques: surveys, questionnaires, and an observation guide, which were applied to students and teachers. According to students’ results of the research they like coloring and drawing the activities presented in each unit the most. Students prefer making projects too; and these must be interesting and related to the topic studied. We have analyzed what students do before, during and after each story: we have that only 56% of teachers review vocabulary before a story and we realized it is not the majority of them, students do a variety of activities before each story but some of them are not done frequently, this means that before reading a story, students do not get prepared enough to have a good reading comprehension skill. Students have affirmed that when they are reading or listening to a story the teacher pauses and explains or they ask questions to the teacher. Within the activities suggested during a story, it is not included to pause and interrupt the process; all the topics we proposed in the survey were checked by the teachers but not in a high percentage as activities they do, it means the majority of teachers do not do it. The objective of stories is that students understand and learn from them, the activities proposed by teachers after reading a story are not helping students to comprehend the readings, only two activities from the ones mentioned match that objective, the rest help them in other aspects but not in improving their reading comprehension. Teachers agreed that this book does not help students to improve their reading comprehension skills in the way they need. Some students said that stories are long, difficult, and boring; it means there is not a definitive set of strategies which are not being taught in the right way. Teachers feel that the book they are using needs more written production and reading comprehension exercises, their suggestion has to be considered because it has direct relation with the improvement of students’ reading comprehension skills however those are not the only things they can do to meet that need. Primary Colors books used at “Servicios Educativos Integrados Speak up Center” do not have enough reading comprehension activities that support English learning through stories. Teachers at “Servicios Educativos Integrados Speak up Center” do not use a variety of resources that help students improve the development of reading comprehension. Primary Colors books have only few interesting activities like games and coloring and draw exercises that students enjoy the most according to their opinion. Students at “Servicios Educativos Integrados Speak up Center” enjoy working with Primary Colors books however they recognize they could be improved with additional material like stickers, cutouts, CDs and worksheets.